Assembly‐In‐Foam Approach to Construct Nanodiamond/Carbon Nanotube Hybrid Monolithic Carbocatalysts for Direct Dehydrogenation of Ethylbenzene to Styrene. Issue 26 (30th June 2022) - Ge, Guifang; Wei, Xiaojing; Guo, Hongchen; Zhao, Zhongkui
Abstract: Sustainable nanocarbon catalysts have made measurable progress in ethylbenzene direct dehydrogenation (DDH). Thanks for the distinctive physical and chemical properties of Nanodiamond (ND), the considerable attention have been paid to diverse catalytic transform processes involving the DDH reaction. However, the powder‐form carbon cannot be directly used in fixed‐bed reactors owing to the resulting huge pressure drop. Herein, inspired by the ship‐in‐boat strategy, we present an ingenious assembly‐in‐foam approach for the preparation of a novel hybrid structured monolithic catalyst featuring an aerogel of sulfur‐doped nanodiamonds/carbon nanotubes hybrid within the macropores of SiC foam (ND−CNT−SDS/SiC) by heating the freeze‐dried macroporous hybrid gels composed of CNT, ND, and SDS in N2 atmosphere. Owing to the promoted NDs dispersion, strengthened mass transfer, and sulfur‐doping, the nanodiamonds/carbon nanotube hybrid foam monolithic catalyst exhibits a terrific catalytic performance with high stability for energy‐saving styrene production from DDH of ethylbenzene reaction, as well as overcoming the shortcomings of application of powder‐formed nanocarbon in heterogeneous catalysis. Furthermore, the emerging Assembly‐in‐Foam way for preparing nanocarbons‐based foam monolithic catalyst towards diverse chemical processes has been paved. Abstract : A facile assembly‐within‐foam strategy was reported to prepare novel nanodiamond−carbon nanotube/SiC monolithic catalyst, featuring macroporous hybrid aerogels within SiC foam, which generates an excellent foam monolithic carbocatalyst for styrene production from direct dehydrogenation of ethylbenzene.